High Risk Primary Percutaneous Coronary Intervention (Pci) in Patient with Acute Stemi Anterior, Chronic Kidney Disease, and Confirmed Covid-19 - Dede Moeswir; Fadhil Muhammad; Putri Nurbaeti (The Avicenna Medical Journal, 2021)
Background: An acute ST-elevation myocardial infarction (STEMI) anterior occurs due to occlusion of left anterior descending artery (LAD) branch of left coronary artery. The occlusion causing transmural myocardial ischemia which in turn to myocardial infarction due to myocardial injury or necrosis. Not only Primary Percutaneous Coronary Intervention (PCI) should be performed in STEMI less than 120 minutes as the risk of the adverse events would increase if exceeding the total ischemic time, but also the procedure can be high risk in patients with multiple clinical factors or comorbidities which can increase the risk of complications.Case Report: We report a case of a 57 years old man who presented Acute STEMI Anterior, Coronary Artery Disease (CAD) 3 Vessel Diseases (VD), Hypertension Heart Disease (HHD), Chronic Kidney Disease (CKD) on Hemodialysis (HD), with COVID-19 confirmed.Results: The left coronary artery was successfully stented by PCI and Coronary Angiogram (CAG) procedures with TIMI 3 flow, minimal bleeding and others complications.